Comparison of Group Logotherapy and Acceptance and Commitment Therapy (ACT) Group Treatment on Pain Catastrophizing in Individuals with Chronic Pain - Andarvafer , Zahra; Rahmanian, Mahdieh; Agahheris, Mojgan; Rafiepoor, Amin; Kordmirza Nikoozadeh , Ezatollah (Mental Health and Lifestyle Journal, 2026)
Chronic pain is one of the most common medical problems worldwide, affecting a large number of individuals who often fail to find adequate treatment. The present study aimed to compare the effects of group logotherapy and group-based Acceptance and Commitment Therapy (ACT) on pain catastrophizing in individuals with chronic pain. This study employed a quasi-experimental design with pretest–posttest, follow-up, and a control group. The study population included all individuals with chronic musculoskeletal pain in the city of Qom who either visited the orthopedic specialist department of Ali ibn Abi Talib Hospital in Qom during the year 2025 or responded to the online recruitment call for the study. A total of 45 participants were purposefully selected and randomly assigned to three groups of 15 participants each, including two experimental groups (ACT group therapy and group logotherapy) and one control group. One experimental group received eight 90-minute sessions of ACT, and the other received eight 90-minute sessions of logotherapy. The control group received no intervention. The measurement instrument was the standardized Pain Catastrophizing Scale (PCS) (Sullivan, 1995). Data were analyzed using repeated-measures ANOVA and Bonferroni post hoc tests. The findings indicated that both ACT group therapy and group logotherapy significantly reduced pain catastrophizing in individuals with chronic pain during the posttest and follow-up phases. Based on the study findings, both ACT and logotherapy can be utilized by clinicians as effective interventions for reducing pain catastrophizing in individuals with chronic pain.